Potensi Bacillus Coagulans dari Serasah Hutan sebagai Probiotik Ayam Broiler - Wizna Wizna; H. Abbas; A. Dharma; P. Kompiang (Universitas Andalas, 2013)
Probiotics are living microorganisms which controls the balance of pathogenic microbes in the digestive tract of cattle through competitive exclusion mechanism which lately has been widely used as a feed aditive both ruminants and poultry . One type of microbes used in probiotics in poultry livestock is a bacterium of the genus Bacillus . Bacillus coagulans (Lactobacillus sporogenes) had the same function as Lactobacillus sp known as probiotics were able to live in the digestive tract and produced some enzymes and antibiotics required by livestock. The method used in this study is an experimental method with a completely randomized design with 6 treatments administered dose level Basillus coagulans were repeated 5 times. Bacillus coagulans administration dose levels are : Do = Control (Provision of physiological saline without bacteria), DI = 0,6.106 CFU/ml, DII = 42.106 CFU/ml, DIII = 45.107 CFU/ml, DIV = 73.108 CFU/ml, DV = 90.1010 CFU/ml. To determine the effect of treatment used analysis of variance completely randomized design pattern and made a real difference obtained Duncan Range Test. The parameters measured were the number of colonies of Bacillus coagulans in the small intestine, feed intake, weight gain, feed conversion, and Income Over Feed Cost (IOFC) of broiler chickens. The results showed the higher dose of Bacillus coagulans were given the better growth of broiler chickens, which at doses 90.1010 CFU /ml chicken rations consume 2679 grams/head with the weight of 1810 g/fish or feed conversion of 1.48 and IOFC 170 g/kg harvest weight or Rp 508 ,-/kg harvest weight. Bacillus coagulans can be used as probiotics to aid digestion and optimal growth of broiler chicken.